2008
DOI: 10.1021/jp711889k
|View full text |Cite
|
Sign up to set email alerts
|

Pure Silica Chabazite Molecular Spring: A Structural Study on Water Intrusion−Extrusion Processes

Abstract: Water intrusion-extrusion isotherms performed at room temperature on hydrophobic pure silica chabazite show that the water-Si-CHA system displays real spring behavior. However, differences in pressure-volume diagrams are observed between the first and the other intrusion-extrusion cycles, indicating that some water molecules interact with the inorganic framework after the first intrusion. (29)Si and especially (1)H solid-state NMR showed the creation of new defect sites upon the intrusion-extrusion of water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 19 publications
6
85
1
Order By: Relevance
“…In Si-chabazite, Trzpit and co-authors [38] found -through water intrusion/extrusion isotherms, 29 Si and 1 H NMR and X-ray powder diffraction -that H 2 O molecules are trapped in the chabazite supercage. Two situations were identified: i) aggregates formed by molecules strongly hydrogen bonded with the framework silanols (formed upon intrusion-extrusion ) and; ii) liquidlike physisorbed molecules, only interacting with other H 2 O molecules.…”
Section: Water Confinement and Condensation In Hydrophobic Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Si-chabazite, Trzpit and co-authors [38] found -through water intrusion/extrusion isotherms, 29 Si and 1 H NMR and X-ray powder diffraction -that H 2 O molecules are trapped in the chabazite supercage. Two situations were identified: i) aggregates formed by molecules strongly hydrogen bonded with the framework silanols (formed upon intrusion-extrusion ) and; ii) liquidlike physisorbed molecules, only interacting with other H 2 O molecules.…”
Section: Water Confinement and Condensation In Hydrophobic Zeolitesmentioning
confidence: 99%
“…[30][31][32][33]. In general, different behaviors can be observed, depending on various physical parameters of the matrix, such as pore size, pore system, channel dimensionality (one-, bi-or three-dimensional) [34][35][36][37], and on the hydrophobic/hydrophilic character of the zeolite [33,38]. According to the reversible or irreversible character of the intrusion-extrusion cycle, ""water -Si-zeolite"" systems are able to restore, absorb or dissipate mechanical energy.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of "zeosil-water" systems has already been studied [7][8][9][10]. More recently this research field was extended to metal-organic framework [11][12][13][14], but also to the intrusion of electrolytes [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For water and hydrophobic silica gels, the confined liquid would remain in the nano-environment, resulting in a significant hysteresis of sorption isotherm [6][7][8][9]. On the contrary, for water and some kinds of hydrophobic zeo lites, water molecules extrude from the nano-pores as soon as the pressure drops, resulting in coincidence sorption isotherm [10][11][12][13][14]. For the former, the mechanical energy is absorbed so the mixture of water and hydrophobic silica gels is used as colloidal damper.…”
Section: Introductionmentioning
confidence: 99%
“…Suciu [6,7] and Qiao [8][9] tried to use colloidal damper for energy absorption. Eroshenko and Patarin [10][11][12][13][14] start to investigate molecular spring material at the beginning of this century. They have affirmed that several kinds of zeolites such as Silicalite-1, SSZ-24, ZSM-22, ZSM-12, DD3R and Si-CHA can be used as the nano-porous material for molecular spring.…”
Section: Introductionmentioning
confidence: 99%